Patterns of growth: self-discovery journeys of female characters in selected women-authored Indian and Nigerian Bildungsromane - Meenachi d/o N Andiappan (Nanyang Technological University, 2024)
In this dissertation, I argue that the emergence of Bildungsroman in India, Nigeria and their diasporas are attempts by postcolonial authors to portray the transformations that occurred during the country’s historical development from a colony to an independent nation state and the ongoing decolonising struggles of the postcolonial nation after independence. I assert that women writers tend to focus on how transformations in the public sphere in the form of political, sociocultural, and economic changes invade the domestic sphere and influence gender and familial relations and impact the development of female protagonists. The aim of this research project is to investigate the complex appropriation of the traditional Bildungsroman by postcolonial women writers and their incorporation of other narrative forms to portray the development journeys and growth patterns of female protagonists in the backdrop of a transforming milieu. Feminist Bildungsromane by Indian writers Attia Hosain, Manju Kapur and Kamala Markandaya and Nigerian writers Zaynab Alkali, Chika Unigwe and Sefi Atta are examined using a combination of different theoretical perspectives. Postcolonial feminism, African feminism and intersectionality are used for a nuanced examination of the multidimensional nature of women’s oppression and a gender lens is included to examine how the authors challenge ideologies and dismantle power structures that contribute to the social and cultural construction of traditional womanhood and the perpetuation of gender stereotypes that create hurdles in the protagonists’ journeys to self-actualisation. In addition, the use of genre criticism illuminates how the authors revise the genre of the Bildungsroman and engage in dialogues with other genres to portray the problematic development of female protagonists in the colonial and postcolonial world. Although written in different historical and sociocultural contexts, the selected novels converge in their incorporation of features of other genres such as the historical novel, autobiography and the memoir and their intervention of the conventions of the traditional Bildungsroman to portray double or triple Bildung and include multiple stories of women. Despite the modifications made to the traditional Bildungsroman, the novels largely retain the realist form and affirm the possibility of self-formation for females even though the journey may be long and laborious. The refusal of all the novels to provide a closed ending indicates that the attainment of complete freedom for a female postcolonial subject is work in progress, like the lengthy and prolonged decolonisation process that ex-colonies are engaged in. Negotiation rather than confrontation with patriarchal limitations, more inclusive politics, female solidarity in the form of friendship and mentorship, empowerment through education and career are some of the solutions that the texts put forward to improve the condition of women.